Enzymatic treatment applied as a final stage in E-globulus kraft pulp bleaching - Sousa, Joana I. T.
BACKGROUNDBrightness stability of bleached chemical pulps is often associated with the final bleaching stages that should provide the removal of chromogenic species responsible for brightness reversion without compromising the papermaking potential. Aiming at promoting higher brightness stability, a partially bleached Eucalyptus globulus pulp (DED) of c. 88% ISO brightness was involved in a study of a final enzymatic stage (X) alternative to conventional chlorine dioxide (D) and hydrogen peroxide (P) bleaching stages (DEDX vs. DEDD and DEDX vs. DEDP). X stage was also applied before and after the final P or D stages (DEDDX/DEDXD and DEDPX/DEDXP) to produce high brightness pulps (c. 91%). RESULTSX stage with xylanase Pulpzyme HC allowed an increase of c. 1.5% in pulp brightness while decreasing the brightness reversion and a concomitant pulp yield loss of only 0.5%. Significant chemical savings were obtained in the final D (70%) or P (45%) stages to achieve targeted final brightness of c. 91%. DEDXD or DEDXP sequences had advantage over DEDDX and DEDPX, respectively, in terms of brightness stability of fully bleached pulps. CONCLUSIONSXylanase interferes with structures responsible for the brightness reversion. X stage allows production of pulp with extra brightness in sequences with a final P stage. (c) 2014 Society of Chemical Industry